Estimating the lifecycle fertility consequences of WWII using bunching - Esmée Zwiers (Tinbergen Institute, 2024)
In the Netherlands, an immediate baby boom followed the end of WWII and the baby bust of the 1930s. I propose a novel application of the bunching methodology to examine whether the war shifted the timing of fertility or changed women's completed fertility. I disaggregate the number of births by age for cohorts of mothers, and estimate counterfactual distributions of births by exploiting that women experienced the war at different ages. I show that the rise in fertility after the liberation did not make up for the "missed" births that did not occur prior to the war, as fertility would have been 9.4% higher in absence of WWII.
Keywords: J11; J13; J18; N34; N44; 330; Lifecycle fertility; bunching; World War II; The Netherlands